2002
DOI: 10.1007/s00234-002-0845-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar peduncle myelinolysis: case report

Abstract: We present a case of bilateral middle cerebellar peduncle myelinolysis, in which the diagnosis modality was MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, the middle cerebellar peduncles can be a ected with or without a pontine lesion. 4 Our patient had both central pontine and bilateral middle cerebellar peduncular lesions (Fig. 3).…”
Section: Extrapontine Myelinolysismentioning
confidence: 72%
“…However, the middle cerebellar peduncles can be a ected with or without a pontine lesion. 4 Our patient had both central pontine and bilateral middle cerebellar peduncular lesions (Fig. 3).…”
Section: Extrapontine Myelinolysismentioning
confidence: 72%
“…Follow‐up MRI on POD 20 showed progressive disease consistent with EPM. Although the involvement of EPM in the cerebellar peduncles is uncommon, such lesions have been reported (21, 22). Despite the radiographic progression of myelinolysis, the ADC calculations showed gradual resolution of demyelination in the pons, corresponding to the patient’s slow clinical recovery marked by increased responsiveness and spontaneous eye opening.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the authors of this study are aware, extrapontine myelinolysis of the cerebellar peduncle has been reported in only one case [5], in which the patient was an alcoholic. We encountered a case of extrapontine myelinolysis in a patient who had received regular hemodialysis as treatment for endstage renal disease.…”
Section: Introductionmentioning
confidence: 89%